Consumer’s purchase intention of ethical fashion. Examining beliefs about fashion industry and attitudes towards ethical fashion - Pollari, Mari (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
Globalization and the developments of supply chain have made inexpensive labor and the low production costs of developing countries available to businesses worldwide. Unfortunately, these developments have also led to the exploitation of human and natural resources. The increasing supply of cheap and fashionable clothing has created a contradiction between consumers’ concerns for sustainability and their purchase behavior in the fashion industry. Since the uncovering of several sweatshop scandals in the 1980’s and 1990’s ethical fashion brands have started to emerge. Ethical fashion has sparked the interest of consumers and studies have shown promising positive attitudes towards it. However, these attitudes have failed to translate into action and purchase behavior of ethical fashion has not reached the expectations. In order to translate the positive attitudes into buying companies must understand consumer’s motivations and reasons behind the purchase decision. The objective of this study is to understand the antecedents behind young consumer’s purchase intention of ethical fashion. The study is based on the theory of planned behavior which has been widely used to study consumer behavior and purchase decisions. The theory has also been used in ethical decision-making and fashion context before. According to the theory, in order to understand purchase intentions consumer’s attitudes toward buying ethical fashion were studied. The theory also states that attitudes are formed from beliefs, thus, consumer’s beliefs about the fashion industry were studied. To contribute to existing research, the effect of sweatshop issues and environmental issues were compared. The data was collected from university students (n=617) with an online survey. The results were analyzed by statistical methods and they revealed that young Finnish consumers hold positive attitudes towards buying ethical fashion as well as positive purchase intentions of ethical fashion. A strong relationship was found between positive attitudes and positive purchase intentions. Also, the more negative consumers’ beliefs of the fashion industry were the more positive their attitudes toward buying ethical fashion were. In contradiction to previous research this study revealed that environmental issues had greater effect on attitudes than sweatshop issues. Interesting differences between consumers were found depending on their field of education. Students from humanities and social sciences held the most negative beliefs as well as most positive attitudes and purchase intentions of ethical fashion.